Molecular epidemiology of mother-to-child transmission of HIV-1 in children at Tygerberg Hospital - Korsman, Stephen Nicolaas Jacques (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MMed (Medical Microbiology))--University of Stellenbosch, 2006.